2019
DOI: 10.1088/1742-6596/1341/3/032023
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antioxidant Analysis of Methanol Extract of Moringa and Celery Leaves

Abstract: Moringa (Moringa oleifera) and Celery (Apium graveolens L) are vegetables and medicinal plants that have excellent benefits for health. The content of secondary metabolites that are very diverse in these two plants has the potential to be developed in other fields. This study aimed to determine the content of secondary metabolites and antioxidant activity of ethanol extract of moringa and celery leaves. The phytochemical analysis using the qualitative parameters of flavonoids, alkaloids, tannins, saponins, phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…All tested phytochemicals are presented in all types of plant part extracts; however, abundance of these phytochemicals varies among plant parts extract types. Leaves showed abundant phytochemicals, which conforms to the previous observation (Natsir et al 2019). In contrast to the findings of Patel et al (2014) in ethanolic extract of leaf, we found moderate presence of glycosides in leaf extract.…”
Section: Discussionsupporting
confidence: 90%
“…All tested phytochemicals are presented in all types of plant part extracts; however, abundance of these phytochemicals varies among plant parts extract types. Leaves showed abundant phytochemicals, which conforms to the previous observation (Natsir et al 2019). In contrast to the findings of Patel et al (2014) in ethanolic extract of leaf, we found moderate presence of glycosides in leaf extract.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of these extracts on the tested fungal species have been evident to lie in their bioactive constituents which include tannins, alkaloids, flavonoids phenols etc. (Anysor et al, 2011;Onegbu et al, 2020) The inhibitory properties of the extracts affect the growth of fungi by affecting their metabolism, which may have resulted in their inability to use the required substrate efficiently (Natsir et al, 2019). This is also in line with the statements by (Wang et al, 2016) who reviewed antimicrobial activity and bioactive compound of Moringa oleifera and (Leone et al, 2015) who reported on the antimicrobial characteristics of Moringa oleifera leaf.…”
Section: Discussionmentioning
confidence: 68%
“…This shows that phenolic compounds from plant extracts contribute more than 50% to antioxidant activity. The results showed that the index antioxidant activities of Pandanus amaryllifolius by IC50 (110.57 ± 36.42 μg / mL) was categorized as moderate scale [54]. The levels of antioxidant power is divided into 4 levels, namely very strong (IC50 <50 μg / mL), strong (IC50 50-100 μg / mL), moderate (IC50 100-250 μg / mL, and weak (IC50 250-500 μg / mL) [55].…”
Section: Antibacterial Of Pandanus Amaryllifolius Roxb Leavesmentioning
confidence: 99%